ИССЛЕДОВАНИЕ ФАКТОРОВ, ВЛИЯЮЩИХ НА ВРЕМЯ ДВИЖЕНИЯ ОБЩЕСТВЕННОГО ТРАНСПОРТА - Кравченя, Ирина; Сушко, Светлана (SWorldJournal, 2022)
One of the quality indicators of commuter passenger transport services is punctuality that is directly related to the well-planned route vehicles schedule. The results obtained in the article allow us to conclude that irrational norms of traffic time of v